A comparative study on structural, optical, photoconductivity properties of In and Al doped ZnO thin films grown onto glass and FTO substrates grown by spray pyrolysis process - Benhaliliba, M.; Benouis, C. E.; Aida, M. S.; Sanchez Juarez, A.; Yakuphanoğlu, Fahrettin; Tiburcio Silver, A. (Elsevier Science Sa, 2010)
A comparative study on In and Al doped ZnO thin films grown onto glass and FTC substrates by spray pyrolysis technique has been done. The obtained results show that the structural shape, crystalline, grain size parameter, transmittance, absorption coefficient and optical band gap and photoconductivity of the ZnO films were changed by the nature of the substrate used. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Zinc oxide; FTO-coated glass; Optical properties; Negative photoconductivity